Music Data Analysis: Foundations and Applications. Edited By C.Weihs, D.Jannach, I.Vatolkin and G.Rudolph. Boca Raton, Florida: CRC Press. 2017. 675 pages. AUD$94.99 (hardback). ISBN978‐1‐4987‐1956‐8. (28th August 2018) - Bulger, David
Abstract : Review of an edited volume covering computational statistical methods in music production, processing, analysis and classification.